2001
DOI: 10.1093/fampra/18.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Lack of mental well-being in 15-year-olds: an undisclosed iceberg?

Abstract: Fifteen-year-olds rarely consult their GP about their emotional well-being, yet, with the GHQ-12, the self-reported rate of psychiatric morbidity was nearly seven times greater than that suggested by these same subjects' medical records. Although the majority of adolescents consult their GP throughout the course of a year, those with mental health problems, including those who attempt suicide, are indistinguishable in the frequency of their GP consultations from adolescents without mental health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 10 publications
2
18
0
1
Order By: Relevance
“…It has been found that adolescents might also experience resistance or hostility and bad attitudes from adults when they attempt to obtain the reproductive health information and services. These circumstances can be attributed to a number of social, religious, cultural, economic, and gender-related factors (Potts et al, 2001). It may not be misleading to state that these factors are present in Nigeria where this study was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that adolescents might also experience resistance or hostility and bad attitudes from adults when they attempt to obtain the reproductive health information and services. These circumstances can be attributed to a number of social, religious, cultural, economic, and gender-related factors (Potts et al, 2001). It may not be misleading to state that these factors are present in Nigeria where this study was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…4,12,13 Only 10% of young people presented with psychological complaints. Despite not presenting for such reasons, a quarter of participants perceived they had a mental illness when asked to evaluate their mental health status.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that despite the burden of disease attributable to mental and behavioral disorders, the majority of consultations to family doctors are for somatic health problems (respiratory and dermatological). 4,12,13 Although many of them would welcome a discussion on these themes, few receive counseling about health-related behaviors in the consultation. [14][15][16] In the US, about 8% of all ambulatory care encounters (specialist and primary care) are with patients in the age group 15 to 24 years.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, according to recent reports, this group of the society benefits the least from programs related to the prevention of psychological diseases (19,20).…”
Section: Introductionmentioning
confidence: 99%